Religious Moderation in the Perspective of Religious Community Organizations of Persatuan Islam (PERSIS) - Isnaeniah, Erni; Nisa, Fitriya Khoirun; Ihyana, Falya Alifa (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This research aims to describe the leadership perspective of the Persatuan Islam (Persis) Branch of Tanjungsari on the concept of religious moderation, analyze its relevance to Emile Durkheim’s structural-functional theory and George Herbert Mead’s symbolic interactionism, and explain its sociological implications for community interaction in Tanjungsari. This study employs a qualitative-descriptive approach using field studies and library research. Data were collected through observation, interviews, and documentation, involving Persis religious leaders and community members as primary data sources, while books, journals, and official documents served as secondary data. The analysis applies sociological interpretation based on Durkheim’s and Mead’s theoretical frameworks.The findings indicate that Persis Tanjungsari understands religious moderation as a social mechanism that fosters harmony while maintaining Islamic orthodoxy. Moderation is practiced in social interactions but not extended to theological compromise. The organization functions as a moral regulator, cultivating tolerance without diluting religious principles. This aligns with Durkheim’s concept of religion as a source of social solidarity and Mead’s view of meaning formation through interaction. This study contributes to the sociology of religion in Indonesia by revealing the internal meaning-making process of moderation within Persis and its implications for community cohesion.